Noah Webster and his words - Ferris, Jeri (Houghton Mifflin Books for children, 2012)
A portrait of the man who wrote the first U.S. dictionary traces his youth as a bookish Connecticut farm boy and his twenty-year effort to write the all-American dictionary that was published in 1828 when he was seventy years old.